2015
DOI: 10.1183/13993003.00263-2015
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for risk of developing active tuberculosis in contacts of TB patients: a prospective cohort study

Abstract: Identifying those Mycobacterium tuberculosis latent-infected individuals most at risk of developing active tuberculosis (TB) using routine clinical and laboratory tests remains a huge challenge in TB control efforts. We conducted a prospective longitudinal study of clinical and laboratory markers associated with the risk of developing active TB in contacts with latent M. tuberculosis infection.HIV-negative household contacts (n=296) of pulmonary TB patients underwent monitoring of clinical features, full blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 40 publications
9
41
1
2
Order By: Relevance
“…We thus provide primary evidence that ex vivo immune signatures in PBMC can discriminate between LTBI and non-TB infected donors, which could potentially be applied as an additional tool to IGRAs for improving the specificity of LTBI diagnosis. Recent studies have also shown differences in whole blood cell counts of infants and adults with various TB status (32, 33). Specifically, a high monocyte/lymphocyte ratio was associated with an increased risk of developing active TB (32, 33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We thus provide primary evidence that ex vivo immune signatures in PBMC can discriminate between LTBI and non-TB infected donors, which could potentially be applied as an additional tool to IGRAs for improving the specificity of LTBI diagnosis. Recent studies have also shown differences in whole blood cell counts of infants and adults with various TB status (32, 33). Specifically, a high monocyte/lymphocyte ratio was associated with an increased risk of developing active TB (32, 33).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown differences in whole blood cell counts of infants and adults with various TB status (32, 33). Specifically, a high monocyte/lymphocyte ratio was associated with an increased risk of developing active TB (32, 33). Thus, we predict that combining whole blood counts to our newly defined ex vivo PBMC signature of LTBI will improve its discriminatory power.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1920s it was shown in a rabbit model that a higher ratio between peripheral blood monocytes and lymphocytes, known as the monocyte/lymphocyte (M/L) ratio, was associated with progressive active TB [137,138]. This finding was confirmed in humans [139,140] and, recently, it was shown that the M/L ratio returned to levels found in healthy donors upon TB cure [141]. This finding may be related to decreased inflammation during effective TB treatment, leading to decreased myelopoiesis in the bone marrow, which is known to be driven by IFN-γ produced during the antimycobacterial response [139,142].…”
Section: Modulation Of Monocytic and Lymphocytic Cell Populationsmentioning
confidence: 97%
“…The use of IFN-γ response to the latency antigen heparin-binding-haemoagglutinin [13,14], immunoprofiling [15,16], gene expression pattern (i.e. interleukin-13 and autoimmune regulator (AIRE)) [17,18] and proportion of peripheral blood monocytes [19] have been studied as possible biomarkers for incipient TB. However, all of these approaches are still confined to research fields and currently have minimal impact on patient management.…”
Section: Introductionmentioning
confidence: 99%